2007
DOI: 10.1002/ejlt.200700022
|View full text |Cite
|
Sign up to set email alerts
|

Protection of fatty acids against ruminal biohydrogenation in cattle

Abstract: The increased need for intestinal absorption of unsaturated fatty acids in cattle is driven mainly by nutritional guidelines that promote reduced intake of saturated fatty acids by humans, and by reports of enhanced animal performance (such as reproductive performance) when additional essential fatty acids are supplied. A duodenal flow dataset was compiled from 25 published studies that provided up to 93 observations on fatty acid intakes and ruminal outflows across a multitude of unprotected and protected fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 51 publications
1
109
1
4
Order By: Relevance
“…The high content of trans-11 18:1 in FO milk (7.1%) confirms that calcium soap protection of fat is incomplete (Jenkins and Bridges, 2007;Shingfield et al, 2013). VA accumulation in milk fat reflects the inhibitory action of n-3 PUFAs present in , 2004).…”
Section: Resultsmentioning
confidence: 81%
“…The high content of trans-11 18:1 in FO milk (7.1%) confirms that calcium soap protection of fat is incomplete (Jenkins and Bridges, 2007;Shingfield et al, 2013). VA accumulation in milk fat reflects the inhibitory action of n-3 PUFAs present in , 2004).…”
Section: Resultsmentioning
confidence: 81%
“…To avoid passage through the gastrointestinal tract, undamaged seeds were treated with NaOH since this is a procedure that can be used readily on the farm and Kirkland et al (1998) showed that NaOH treatment of LSs could increase the C18:3n-3 proportion of milk. The efficacy of amides of camelina fatty acids as a ruminal protection strategy was also examined as the potential of this strategy has been demonstrated for soybean (Jenkins and Bridges, 2007). The oil from the camelina seeds had a similar fatty acid composition to that reported by Crowley and Frö hlich (1998), which was expected, as the camelina was grown under similar environmental and agronomic conditions.…”
Section: Discussionmentioning
confidence: 77%
“…The challenges associated with extensive biohydrogenation have been addressed by others with the use of ruminally protected fatty acids. Specifically, in their review, Jenkins and Bridges (2007) reported successful protection of fatty acids from biohydrogenation using several methods including prilling, calcium soaps of fatty acids, formaldehyde treatment and fatty acyl amides. Therefore, results could have differed if ruminally protected sources of linoleic and linolenic acid were provided in the diet.…”
Section: Discussionmentioning
confidence: 99%